2021
DOI: 10.3390/polym13050686
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Emission Properties and Thermogravimetric Analysis of Ceramic-Embedded Polyurethane Films

Abstract: The far-infrared ray (FIR) is one kind of electromagnetic wave employed for numerous bio-interactive applications such as body thermoregulation, infrared therapy, etc. Tuning the FIR-emitting property of the functional textile surface can initiate a new horizon to utilize this property in sportswear or even smart textiles. Ceramic particles were studied for their unique ability to constantly emit FIR rays. The purpose of this research is to characterize the FIR emission properties and the thermogravimetric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Digestion of protein eminently takes place in the gut just after the stomach, with the action of hydrochloric acid, and due to size limitations, only smaller peptides and amino acids are permitted to access through the gut wall to be absorbed and become available for growth (Wu et al, 2009). The water inside the gut remains inactive and, in general, has no direct role, except facilitating gut microbiota and maintaining homeostasis (Laforenza, 2012;Giatsis et al, 2015); however, in the presence of silica NP, water molecules within the gut may become activated (Figure 2A) with the influence of a higher infrared emissivity of silica NP (Faisal et al, 2021). A similar indication with Tourmaline (Borosilicate minerals) NP concluded that radiation emissivity from NP can modulate the structure of water clusters into smaller molecules through breaking hydrogen bonds (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Digestion of protein eminently takes place in the gut just after the stomach, with the action of hydrochloric acid, and due to size limitations, only smaller peptides and amino acids are permitted to access through the gut wall to be absorbed and become available for growth (Wu et al, 2009). The water inside the gut remains inactive and, in general, has no direct role, except facilitating gut microbiota and maintaining homeostasis (Laforenza, 2012;Giatsis et al, 2015); however, in the presence of silica NP, water molecules within the gut may become activated (Figure 2A) with the influence of a higher infrared emissivity of silica NP (Faisal et al, 2021). A similar indication with Tourmaline (Borosilicate minerals) NP concluded that radiation emissivity from NP can modulate the structure of water clusters into smaller molecules through breaking hydrogen bonds (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ceramic particles, such as TiO 2 , are known to imbue textiles with antibacterial properties [ 40 , 41 ]. The Ge-Ti-π textile, which contained titanium as one of the fillers, exhibited a significant efficacy against S. aureus bacteria [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the addition of ceramic particles to polyurethane films, Faisal et al showed that TiO 2 has the highest FIR emissivity among other ceramic particles such as Al 2 O 3 . The study also exhibited that TiO 2 -embedded PU films have a comparable contact angle and mechanical properties to Al 2 O 3 - and SiO 2 -doped PU films [ 41 ]. In biomedical applications, titanium combined with polyimide is successfully used as an implant material owing to the biocompatibility of the components [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the FIR radiation in the wavelength range of 4–14 µm produces beneficial effects for human health [ 1 , 2 , 3 ] and plants [ 4 , 5 ]. The human body itself, according to Planck’s black-body emission law, emits IR radiation with a peak wavelength of about 9.3 µm [ 6 ].…”
Section: Introductionmentioning
confidence: 99%